Analisis Keputusan Nasabah Memilih Bank Mandiri Syariah Cabang Medan Krakatau Melalui Faktor Kepercayaan dan Religiusitas - Bayu Akbar Pradana; Basana Lumban Gaol; Distra Wardah Fadillah Fadillah (Inovatif: Jurnal Ekonomi, Manajemen, Akuntansi, Bisnis Digital dan Kewirausahaan, 2023)
This study aims to examine the analysis of customer decisions to choose Bank syariah cabang medan krakatau through the factors of trust and religiosity. The study was conducted on 96 respondents, especially Bank syariah cabang medan krakatau customers. The results of this study indicate: The results of the first hypothesis testing show that the variable trust with interest is not proven to have a significant effect on interest, by showing a coefficient value, namely. This shows that the trust variable does not have a significant effect on the interest variable , The Religiosity variable with interest is proven to have a significant effect on interest, namely, namely. This shows that the variable of religiosity affects the interest variable. The trust variable and customer decision proved to be influential and significant on consumer loyalty, namely, namely. This shows that the trust variable affects the customer decision variable. The variable of religiosity and customer decision proved to be influential and significant towards customer decisions, namely, namely. This shows that the variable of religiosity has an effect on customer decision variables., namely This shows that the interest variable affects the customer decision variable .